Effects of Biodiesel Saturation Degrees on NOx Emission and FTIR Spectroscopy - Mohd Fareez Edzuan, Bin Abdullah; Nadzirah, Binti Madzrol; Rolf Willa, Anak Patrick Sandin (JASPE, 2016)
The Fourier Transform Infrared (FTIR) spectroscopic characteristics of biodiesel produced from vegetable oils with different saturation degree was investigated in this study. Unsaturation degree, usually determined by the Iodine Value (IV) indicates the sum of double bonds, triple bonds and/or rings. In this work, biodiesels were produced by canola oil, palm oil and coconut oil that have saturation degree of 7.0 wt%. 45.6 wt% and 81.5 wt%, respectively. Biodiesel blends of B10, B15 and B20 were tested in a direct injection diesel engine and the NOx emissions were measured with a flue gas analyser. The NOx emission was increased in all biodiesel cases, where the NOx emission seems to be proportional with the biodiesel unsaturation degree. The FTIR spectroscopy of each biodiesel was analysed with FTIR spectrometer. Each biodiesel produced different FTIR spectroscopy characteristics and the double bond of C=O was the most abundant in highly unsaturated canola oil methyl ester which suggested that FTIR spectroscopy can be suitable to analyse biodiesel characteristics.